2021
DOI: 10.1200/jco.20.01894
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, Randomized Study of Dual Human Epidermal Growth Factor Receptor 2 (HER2) Blockade With Lapatinib Plus Trastuzumab in Combination With an Aromatase Inhibitor in Postmenopausal Women With HER2-Positive, Hormone Receptor–Positive Metastatic Breast Cancer: Updated Results of ALTERNATIVE

Abstract: PURPOSE Human epidermal growth factor receptor 2 (HER2) targeting plus endocrine therapy (ET) improved clinical benefit in HER2-positive, hormone receptor (HR)–positive metastatic breast cancer (MBC) versus ET alone. Dual HER2 blockade enhances clinical benefit versus single HER2 blockade. The ALTERNATIVE study evaluated the efficacy and safety of dual HER2 blockade plus aromatase inhibitor (AI) in postmenopausal women with HER2-positive/HR-positive MBC who received prior ET and prior neo(adjuvant)/first-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 31 publications
2
71
0
3
Order By: Relevance
“…While showing less responsiveness to the combination of chemotherapy plus anti-HER2 agents as compared to the HR negative counterpart, results with the combination of anti-HER2 agents and non-steroidal aromatase inhibitors (NSAI) have been quite disappointing with a mPFS not exceeding 4.8 months with trastuzumab and anastrozole and 8.2 months with lapatinib and letrozole as first-line treatment [6,7]. The recently updated ALTERNATIVE trial, which investigated the addition of lapatinib, trastuzumab, or both agents to a NSAI, showed a significant improvement in mPFS for the double HER2 blockade vs trastuzumab plus NSAI (11 vs 5.6 months) [15]. On the other hand the PERTAIN trial reported a mPFS of 21.7 months in the arm with the double HER2 blockade with pertuzumab and trastuzumab plus a NSAI, which was not only significantly higher than that reported by the trastuzumab plus NSAI combination but, more importantly, was similar to that reported in patients who had received chemotherapy before endocrine therapy (mPFS = 18.9 months) [16].…”
Section: Discussionmentioning
confidence: 99%
“…While showing less responsiveness to the combination of chemotherapy plus anti-HER2 agents as compared to the HR negative counterpart, results with the combination of anti-HER2 agents and non-steroidal aromatase inhibitors (NSAI) have been quite disappointing with a mPFS not exceeding 4.8 months with trastuzumab and anastrozole and 8.2 months with lapatinib and letrozole as first-line treatment [6,7]. The recently updated ALTERNATIVE trial, which investigated the addition of lapatinib, trastuzumab, or both agents to a NSAI, showed a significant improvement in mPFS for the double HER2 blockade vs trastuzumab plus NSAI (11 vs 5.6 months) [15]. On the other hand the PERTAIN trial reported a mPFS of 21.7 months in the arm with the double HER2 blockade with pertuzumab and trastuzumab plus a NSAI, which was not only significantly higher than that reported by the trastuzumab plus NSAI combination but, more importantly, was similar to that reported in patients who had received chemotherapy before endocrine therapy (mPFS = 18.9 months) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of dual HER2 blockade, which utilizes different HER2‐targeted agents with complementary mechanisms to overcome drug resistance, has been researched and put into clinical practice in HER2‐amplified breast cancer 10,11 . In the NeoALTTO trial, the combination of trastuzumab and lapatinib plus chemotherapy as neoadjuvant therapy significantly improved rates of pathological complete response in early breast cancer 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the NeoALTTO trial, the combination of trastuzumab and lapatinib plus chemotherapy as neoadjuvant therapy significantly improved rates of pathological complete response in early breast cancer 10 . The ALTERNATIVE trial showed that dual HER2 blockade with lapatinib and trastuzumab plus an aromatase inhibitor had superior PFS benefit vs trastuzumab plus aromatase inhibitor (11 vs 5.6 months, HR 0.62 (0.45 to 0.88), P =.0063) in metastatic breast cancer 11 . The authors concluded that this combination offered a safe treatment regime for patients; its adverse events mainly Grade 1‐2 diarrhea, rashes, nausea, and paronychia 11 …”
Section: Discussionmentioning
confidence: 99%
“…With the exception of one single case report [ 22 ], there are no clinical studies that used anti-HER2 compounds in a single or multiple-agent approach in CDC. A large plethora of data indicates that solid tumors with HER2 gene amplification respond to an anti-HER2-targeted therapy [ 26 , 27 , 28 , 29 ], with an improvement in clinical outcomes. Based on this principle, our study provides preliminary evidence in support of testing anti-HER2 therapy in CDC.…”
Section: Discussionmentioning
confidence: 99%